Imaging neuroinflammation in vivo in a neuropathic pain rat model with near-infrared fluorescence and ¹⁹F magnetic resonance. - Kiran Vasudeva (Public Library of Science (PLoS), 2014)
Chronic neuropathic pain following surgery represents a serious worldwide health problem leading to life-long treatment and the possibility of significant disability. In this study, neuropathic pain was modeled using the chronic constriction injury (CCI). The CCI rats exhibit mechanical hypersensitivity (typical neuropathic pain symptom) to mechanical stimulation of the affected paw 11 days post surgery, at a time when sham surgery animals do not exhibit hypersensitivity. Following a similar time course, TRPV1 gene expression appears to rise with the hypersensitivity to mechanical stimulation. Recent studies have shown that immune cells play a role in the development of neuropathic pain. To further explore the relationship between neuropathic pain and immune cells, we hypothesize that the infiltration of immune cells into the affected sciatic nerve can be monitored in vivo by molecular imaging. To test this hypothesis, an intravenous injection of a novel perfluorocarbon (PFC) nanoemulsion, which is phagocytosed by inflammatory cells (e.g. monocytes and macrophages), was used in a rat CCI model. The nanoemulsion carries two distinct imaging agents, a near-infrared (NIR) lipophilic fluorescence reporter (DiR) and a ¹⁹F MRI (magnetic resonance imaging) tracer, PFC. We demonstrate that in live rats, NIR fluorescence is concentrated in the area of the affected sciatic nerve. Furthermore, the ¹⁹FF MRI signal was observed on the sciatic nerve. Histological examination of the CCI sciatic nerve reveals significant infiltration of CD68 positive macrophages. These results demonstrate that the infiltration of immune cells into the sciatic nerve can be visualized in live animals using these methods.